2020
DOI: 10.21831/pep.v24i2.32547
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Math national-standardized school exam test items in junior high school: What must be considered?

Abstract: National Standardized School Exam (USBN) is used to determine Student’s graduation. This research aims to determine the characteristics of items for Math USBN in SMP on grade 9. This kind of research is a descriptive-explorative quantitative research. The data collected is a USBN test instrument at SMP Negeri 3 Pati and participants' answers, which are collected by documentation. The USBN instrument was validated by experts and the characteristic items of USBN instrument were analyzed using the classical test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Such type of error that makes student's test score unpredictable can arise due to students, test-specific, or scoring specific factors (Wells & Wollack, 2003). In a study conducted by Argianti and Retnawati (2020), the students' scores obtained from a test used in national-standardized school examination was reliable, meaning that this result is consistent with our result. In another study (Sampouw & Retnawati, 2020), however, showed a contrast result, in which it was found that the scores obtained from the test used in the examination was unreliable.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Such type of error that makes student's test score unpredictable can arise due to students, test-specific, or scoring specific factors (Wells & Wollack, 2003). In a study conducted by Argianti and Retnawati (2020), the students' scores obtained from a test used in national-standardized school examination was reliable, meaning that this result is consistent with our result. In another study (Sampouw & Retnawati, 2020), however, showed a contrast result, in which it was found that the scores obtained from the test used in the examination was unreliable.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to this focus, the results of our study revealed that more than half of all multiple-choice items performed well in distinguishing students who took the test based on their score assumed to reflect their competence. The previous study focusing on investigating the characteristics of a mathematics test and its items used in the national-standardized school examination (Argianti & Retnawati, 2020) has also shown similar results in terms of the number of items that have good discriminating power. Furthermore, a study conducted by Sampouw and Retnawati (2020) which has a similar focus to our study obtained a similar result with what we have found that of 30 multiple-choice items, one item has a negative discrimination coefficient.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations